Commparative Gross Morphometrical Studies on Urinary System of Aseel and Vanaraja Breeds of Poultry - Kumar, Bhupendra; Ingole, S P; Chaurasia, Durga (Indian Journal of Veterinary Anatomy, 2014)
The present experiment was conducted on 28 apparently healthy birds of Aseel and Vanaraja breeds ofpoultry which were divided into grower and adult groups. Each kidney was divided into cranial, middle and caudaldivisions by the grooves present on the ventral surface. In Vanaraja grower as well as in adult, weight, volume andmaximum width of kidneys and ureter were highly significant than Aseel bird. The percentage contribution ofweight of kidney to body weight was more in Vanaraja grower than Aseel. While, in adult bird it was more in Aseelthan Vanaraja. The ureter had two parts, renal and pelvic. Highly significant difference was observed in theweight, length and volume of both the ureters of Vanaraja grower and adult than Aseel.